Penggunaan Media Pembelajaran Berbasis Wordwall untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti di SMA Negeri 7 Sarolangun - Safitri, Nurvika; Halomoan, Halomoan (YASIN, 2025)
This study is motivated by the importance of learning media in supporting the effectiveness of Islamic Religious and Character Education instruction, particularly for eleventh-grade students in Phase F at SMA Negeri 7 Sarolangun. The main issue identified is the suboptimal use of instructional media, which has led to low student learning outcomes. The purpose of this study is to determine the differences in learning outcomes between the experimental class using Wordwall-based learning media and the control class that did not use this media. The method employed is quantitative with a quasi-experimental design. The research population consists of all eleventh-grade Phase F students, totaling 303 individuals. The sampling technique used was purposive sampling, with two classes selected as samples: class XI FC1 as the experimental group using Wordwall and class XI FE1 as the control group without the use of such media, each comprising 32 students. The results show an improvement in learning outcomes in the experimental group using Wordwall compared to the control group. The conclusion of this study is that the use of Wordwall-based learning media is proven effective in enhancing student learning outcomes in Islamic Religious and Character Education. The implications of this study highlight the need for integrating interactive digital media into the learning process to create a more engaging classroom environment and facilitate a more comprehensive understanding of the material.